Jameson and postmodernism - Marcelino, Giovanna Henrique (Universidade Estadual de Campinas, 2019)
This article aims to give a panoramic view of Fredric Jameson’s interpretation of postmodernism. The central objective is to retrace how this concept was used by the author in the 1980s in his effort to periodize contemporary capitalism and map a series of systemic redefinitions and significant changes in social, culturaland subjective life, increasingly marked by fragmented and ‘presentified’ experiences. Therefore, two essays that condense the author’s diagnoses will be analyzed: Periodizing the 60s and Postmodernism, the cultural logic of late capitalism, both written in 1984. With this, it is intended to ascertain how the work of Jameson, in its own effort to update Marxist theory, raises original elements to consider contemporary capitalist society and its main social symptoms.